Theoretical modeling study of the reaction H + CF4 →HF + CF3 - Cobos, Carlos Jorge (2021)
The high-temperature hydrogenation of CF4 in mixtures of CF4 and H2 is assumed to involve the reaction H + CF4 → HF + CF3. The hydrogen atoms here are either formed by the reaction of F and CF3 (i.e., the products of the thermal dissociation of CF4) with H2, or by the thermal dissociation of H2. In the former case, a complicated chain process is started, while the reaction proceeds in a more direct way in the latter. This article determines the rate constant of the reaction H + CF4 → HF + CF3, characterizing its transition state by quantum-chemical methods.Over the temperature range 1000–3000 K, the most accurate results for the rate constant can be represented in the form 1.64 × 1014 (T/1000 K)1.95 exp(−178.8 kJ mol–1/RT) cm3 mol–1 s–1, based on coupled cluster theory extrapolated to the complete basis set limit, and incorporating vibrational anharmonicity, electron correlation through CCSDT(Q), and relativistic and non-Born–Oppenheimer effects.